A review on clinical decision support systems in healthcare - Al-Badareen, Anas Bassam; Selamat, Mohd Hasan; Samat, Mukushev; Nazira, Yskak; Akkanat, Orynbayeva (Advanced Institute of Convergence Information Technology, 2014)
Expert systems are widely used in healthcare for predicting and diagnosing diseases. Several efforts have been made to help diagnose diseases, and to identify their codes, signs and symptoms. However, abnormal findings, social circumstances and external causes of diseases in the psychological arena are a huge burden of illness in the community and still a complicated task. Several intelligent techniques based on different rules are used in developing CDSS. Therefore, further investigation on the current state of the field is required in order to identify the related issues and the future directions. This study intends to analyze the current state of the expert systems’ development for psychodiagnostics. That provides a comprehensive background of the available methods, techniques and issues related to CDSS.